1996
DOI: 10.1007/s002800050475
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour evaluation of dolastatins 10 and 15 and their measurement in plasma by radioimmunoassay

Abstract: Dolastatins 10 and 15 are small peptides isolated from the marine sea hare Dolabella auricularia that have been shown to interact with tubulin. Their growth-inhibitory properties were compared using panels of human ovarian and colon-carcinoma cell lines. Both agents were very potent inhibitors of cell growth, with dolastatin 10 being an average of 9.1-fold more potent than dolastatin 15 [mean 50% inhibitory concentrations (IC50 values) 2.3 x 10(-10) and 2.1 x 10(-9) M, respectively; P < 0.05] and more potent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…alkaloids [6]. Dolastatin-10 is a potent inhibitor of cell growth in a variety of solid tumor cell lines, including gastrointestinal cancer cell lines, as well as in several solid tumor xenograft models [5,[7][8][9]. Myelosuppression was dose-limiting in phase I trials [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…alkaloids [6]. Dolastatin-10 is a potent inhibitor of cell growth in a variety of solid tumor cell lines, including gastrointestinal cancer cell lines, as well as in several solid tumor xenograft models [5,[7][8][9]. Myelosuppression was dose-limiting in phase I trials [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of MXRs in tissues involved in absorption, secretion and barrier functions in aquatic invertebrates (Bard 2000) suggests that they may play a role in the prevention of dietary xenobiotic absorption. Several studies have also identified marine natural products from algae, tunicates, sea hares and gorgonians that may be substrates for multixenobiotic resistance proteins (Suganuma et al 1988, Chambers et al 1993, Williams & Jacobs 1993, Aherne et al 1996, Quesada et al 1996, Schroder et al 1998, Tanaka et al 2002, suggesting that the pool of potential substrates in marine ecosystems may be extensive. Given this evidence, the constitutive or inducible expression of MXRs in marine consumers may serve a protective role against a range of allelochemically-rich prey.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies showed that this agent binds to tubulin and strongly suppresses microtubule dynamics in a unique manner by suppressing the rate of growth of microtubules more than the rate of shortening thus enhancing the frequency of rescue with little effect on the frequency of catastrophe (32). However, cemadotin is a weak agonist for the angiotensin II type 1 receptor and produced a dose-dependent increase in diastolic blood pressure preclinically (33). Unfortunately, this translated into dose-limiting cardiovascular toxicities in the clinic, including myocardial infarction, peripheral edema, and hypertension (9 -12), all of which were associated with the magnitude of peak blood levels of the parent drug or its metabolites (34).…”
Section: Discussionmentioning
confidence: 99%